2020
DOI: 10.3390/nu12071991
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Low Doses of a Cod Protein Hydrolysate on Glucose Regulation and Lipid Metabolism in Adults with Metabolic Syndrome: A Randomized, Double-Blind Study

Abstract: The risk of cardiovascular diseases and type 2 diabetes mellitus are increased in subjects with metabolic syndrome (MetS), and hydrolyzed fish protein may have favorable effects on metabolic health. Here, we investigated the effect of 8 weeks supplementation with 4 g of cod protein hydrolysate (CPH) on glucose metabolism, lipid profile and body composition in individuals with MetS in a double-blind, randomized intervention study with a parallel-group design. Subjects received a daily supplement of CPH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Nevertheless, there have been multiple studies recently published investigating the antidiabetic and satiating effect of a cod protein hydrolysate; however, there appears to be no significant effect on plasma hormones, blood glucose, or satiety with one study reporting a reduction in plasma insulin. [35,[89][90][91] Initially this appears to be due to a very low dosage regimen (a maximum of 4 g per day) but a separate study performed by Hovland et al showed an effect on glucose tolerance by a cod protein supplement through ingestion of 2.5 g per day for 8 weeks. [92] The important differentiation between these studies is likely that Hovland et al used an unhydrolyzed cod protein supplement, highlighting that the bioactivity of the protein is impacted by the hydrolysis process, and in this case hydrolysis may have negatively impacted the bioactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there have been multiple studies recently published investigating the antidiabetic and satiating effect of a cod protein hydrolysate; however, there appears to be no significant effect on plasma hormones, blood glucose, or satiety with one study reporting a reduction in plasma insulin. [35,[89][90][91] Initially this appears to be due to a very low dosage regimen (a maximum of 4 g per day) but a separate study performed by Hovland et al showed an effect on glucose tolerance by a cod protein supplement through ingestion of 2.5 g per day for 8 weeks. [92] The important differentiation between these studies is likely that Hovland et al used an unhydrolyzed cod protein supplement, highlighting that the bioactivity of the protein is impacted by the hydrolysis process, and in this case hydrolysis may have negatively impacted the bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there have been multiple studies recently published investigating the anti‐diabetic and satiating effect of a cod protein hydrolysate; however, there appears to be no significant effect on plasma hormones, blood glucose, or satiety with one study reporting a reduction in plasma insulin. [ 35,89–91 ] Initially this appears to be due to a very low dosage regimen (a maximum of 4 g per day) but a separate study performed by Hovland et al. showed an effect on glucose tolerance by a cod protein supplement through ingestion of 2.5 g per day for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Energy and protein intake from the supplement were added to the end of study dietary records (CPH group: 44 kcal, 4 g protein; placebo group: 46.5 kcal, 0 g protein). Details about the end of study energy intake is reported in a previous publication [30]. Calculations of energy and macronutrient intake were determined using "Kostholdsplanleggeren" (Norwegian Food Safety Authority, Norwegian Directorate of Health, Oslo) [34].…”
Section: Study Visitsmentioning
confidence: 99%
“…The level of significance was set to p < 0.05. A power calculation was not done in the original study due to lack of data to base it upon [30]. Therefore, no estimation of sample size of the current measurements was done prior to the study.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation